(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The rapid growth of AI writing assistants has changed language learning, but there are still gaps in understanding how learners use these tools effectively and perceive feedback from them to enhance their learning skills. This thesis investigates language learners’ interactions with an AI writing assistant called "Type," identifying prompt types and understanding their perceptions for educational purposes. It is a mixed-methods study examining the interaction between English as a Foreign Language (EFL) learners and "Type." Data was collected from 27 male university learners in Saudi Arabia who used "Type" for writing tasks, with pre- and post-surveys assessing their experiences with AI-assisted writing. Findings identified two main themes: anticipated and unexpected interactions. The study explores the types of prompts used, including style, grammar, and word count prompts. While most participants express satisfaction with the tool’s ability to improve writing skills, the study suggests that future research should expand the sample size and examine the level of proficiency learners have with AI tools. It is crucial to identify the specific errors learners make and analyze the limitations of each AI tool in the learning process.